y'' + 3y' + 2y = 1/( 1 + ex )
Solution:
y'' + 3y' + 2y =0
k2+3k+2=0
k1=-1,k2=-2
y0(x)=c1e-x+c2e-2x
y'' + 3y' + 2y = 1/( 1 + ex )
y(x)=c1(x)e-x+c2(x)e-2x
Let
c1'(x)e-x+c2'(x)e-2x=0,
-c1'(x)e-x-2c2'(x)e-2x=1/( 1 + ex).
Then
c2'(x)=-c1'(x)ex => c1'(x)=ex/(1+ex) => c1(x)="\\int"ex/(1+ex) dx="\\int" d(1+ex)/(1+exl)=ln(1+ex)+c1
c2'(x)=-e2x/(1+ex)=> c2(x)= -∫e2x/(1+ex) dx=-"\\int"(ex+1-1)d(1+ex)/(1+ex)=-"\\int" (1-1/(1+ex))d(1+ex)=
=-(1+ex)+ln(1+ex)+c2
y(x)=c1(x)e-x+c2(x)e-2x=(ln(1+ex)+c1)e-x+(-(1+ex)+ln(1+ex)+c2)e-2x=
=(c1-1)e-x+(c2-1)e-2x+e-xln(1+ex)+e-2xln(1+ex).
Let c1-1->c1, c2-1->c2.
Answer:
y(x)=c1e-x+c2e-2x+e-xln(1+ex)+e-2xln(1+ex).
Comments
Leave a comment